The Model Of Passenger Prediction Of Ahmad Yani Airport Semarang, Route Semarang – Jakarta - Agus Muldiyanto (International Conference on Coastal and Delta Areas, 2017)
Air transportation demand for the passengers showed an increasing number for about ±11,5% from 1993 until 1997. Within assumption the number of passengers in 2020 is known, so that the dominant parameter and to fulfill those means, can be calculated. The Model of Air Transportation Demand for the passengers in Ahmad Yani Airport is analyzed by regression analysis, based on route of the plains, and we choose the dominant route, which is Semarang-Jakarta. Service authority is restricted by the impact of space and time by nearest authority, which are in Solo by Adi Sumarmo Airport, in Yogyakarta by Adisucipto Airport and Cilacap by Tunggul Wulung Airport. Based on services area and the data of social-economic condition for service area, a model of passenger demand is created for those two main routes within amount for two main route either departure or arrival as dependet variable (Y) and data of sosio-economic condition from 19881997 as independent variable. From the model, PDRB variable (X2) is very dominant on equation for route of Semarang-Jakarta Because of monetary crisis from the middle of 1997 until now, the model from data in 1988-1997 is only use basic to get equation with the data from 1998-1999 mend to have the valid result appropriately. By using equations, the quantity of passengers in Ahmad Yani Airport can be predicted, the result total route in 2020 on quantity is still below than in 1997, so that all the infrastructure unnecessarily added. Keyword: passengers, air transportaion, route